Use of lipid‐lowering therapies in patients with chronic kidney disease and atherosclerotic cardiovascular disease: 2‐year results from Getting to an imprOved Understanding of Low‐Density lipoprotein cholesterol and dyslipidemia management (GOULD). Issue 12 (19th September 2022) - Shaik, Aleesha; Kosiborod, Mikhail; de Lemos, James A.; Gao, Qi; Mues, Katherine E.; Alam, Shushama; Bhatt, Deepak L.; Cannon, Christopher P.; Ballantyne, Christie M.; Rosenson, Robert S.; ,
Abstract: Background: Chronic kidney disease (CKD) is a known risk factor of atherosclerotic cardiovascular disease (ASCVD). Per the 2018 American Heart Association/American College of Cardiology cholesterol guidelines, high‐risk ASCVD patients with CKD and low‐density lipoprotein cholesterol (LDL‐C) levels  ≥ $\ge $  70 mg/dL should take a high‐intensity statin with ezetimibe and/or a proprotein convertase subtilisin/kexin type 9 inhibitor (PCSK9i). Objective/Methods: We examined the changes in use of lipid lowering therapies (LLT) over two years in 3304 patients with ASCVD and CKD in the G etting to an impr O ved U nderstanding of L ow‐ D ensity Lipoprotein Cholesterol and Dyslipidemia Management ( GOULD ) observational cohort study. Results: Of those with eGFR <60 ml/min/1.73 m 2, 21.6% (171/791) had intensification of LLT while 10.4% (82/791) had de‐escalation of LLT. Notably, 61.6% (487/791) had no change in LLT regimen over 2 years. Statin use was 83.2% (785/944) at baseline and 80.1% (634/791) at 2 years. Statin/ezetimibe use increased from 2.9% (27/944) to 4.9% (39/791). Statin discontinuation at 2 years was greater with lower eGFR levels across all cohorts. Conclusion: Despite the recommendations of multiscociety guidelines, statin use, while high, is not ubiquitous and rates of high‐intensity statin and ezetimibe use remain low in patients with CKD. There remains a significant opportunity to optimize LLT and achieve atheroprotective cholesterol levels in the CKD population.